P30 Developing a methodological framework for organisational case studies: a rapid review and consensus development process. (13th September 2016) - Rodgers, M; Thomas, S; Harden, M; Parker, G; Street, A; Eastwood, A
Abstract : Background: Organisational case study proposals can be poorly articulated and methodologically weak, raising the possible need for publication standards in this area. This rapid review and Delphi consensus process sought to develop reporting standards for organisational case study research, with particular application to the UK National Health Service (NHS). Methods: The reporting standards were developed in three stages: 1) Rapid evidence synthesis of the existing literature. 2) A modified Delphi consensus. 3) Application of the high-consensus Delphi items to a sample of organisational case studies to assess their feasibility as reporting standards. Results: 103 unique reporting items were identified from 25 methodological texts; eight example case studies and 12 exemplar case studies did not provide any additional unique items. Thirteen items were ultimately rated as "Should be reported for all organisational case studies" by at least 70% of respondents, with the degree of consensus ranging from 73% to 100%. As a whole, exemplar case studies (which had been provided by the project funder as examples of methodologically strong projects) more consistently met the high-consensus Delphi items than did case studies drawn from the literature more broadly. Conclusion: The high-consensus items were translated into a set of 13 reporting standards that aim to improve the consistency and rigour and reporting of organisational case study research, thereby making it more accessible and useful to different audiences. We will present the final list of reporting items.